Empowering Local Communities: Promoting Financial Management in Village-Owned Enterprises (BUM Desa) for Sustainable Tourism Development - Hakiki, Moh. Saiful; Adinugroho, Mukhtar; Fajariansyah, Muhammad Dwi; Safiq, Moh. Nur (UKInstitute, 2023)
Local communities have increasingly become players that have significant roles in the tourism sector, utilizing their unique cultural and natural resources to attract visitors and stimulate local economic growth. Village-Owned Enterprises (BUM Desa) play a crucial role in driving sustainable tourism development by allowing local communities to actively participate in managing and benefiting from tourism activities. However, effective financial management within these enterprises remains a critical aspect that requires attention and improvement. This journal manuscript presents the outcomes of a community service activity conducted to address the financial management challenges faced by Village-Owned Enterprises in the tourism sector. The community service activities involved a series of workshop sessions aimed at providing practical guidance and insights to BUM Desa representatives. These sessions were supplemented by the publication of a book titled